Geoconservation in Portugal with emphasis on the geomorphological heritage - Brilha, J. B. (2020)
Geoconservation in Portugal has been gaining impor- tance, particularly during the last decade. The inventory of geosites with international and national scientific relevance is now complete, and the national legislation concerning nature conservation includes the management of geoheritage. Forty-three per cent of the inventoried geosites are geomorphosites, showing the importance of this type of geological heritage in the Portuguese natural heritage. The geoscientific community is slowly recog- nizing geoconservation as an emergent component of the geosciences. The existence of four UNESCO Global Geoparks in Portugal is also an example of the country’s involvement in the international geoconservation scene.